Perbedaan Gender pada Hubungan Person Job Fit dan Organizational Fit dengan Kinerja dan OCB - Darmawati, Arum; Indartono, Setyabudi (JURNAL ILMU MANAJEMEN, 2015)
Studies on gender are largely investigated by scholars, included investigation on work achievement. However few researchers explore different gender on personal fit influence intra and extra role performance. Hence, this study was aimed to investigate different gender on Person Job Fit and organizational fit related to task performance and organizational citizenship behavior (OCB). Moderation effects of gender are included to test those relationships. The result shows that male and female are equal on the relationship between Person Job Fit and task performance and between personal organizational fit and OCB. Implication for the result and suggestion for future research are discussed.